2016
DOI: 10.1016/j.cois.2016.02.013
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of insect germline specification strategies

Abstract: The establishment of the germline is essential for sexually reproducing organisms. In animals, there are two major strategies to specify the germline: maternal provision and zygotic induction. The molecular basis of the maternal provision mode has been well characterized in several model organisms (fly, frog, fish, and nematode), while that of the zygotic induction mode has mainly been studied in mammalian models such as the mouse. Shifts in germline determination modes occur unexpectedly frequently and many s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 64 publications
(96 reference statements)
1
7
0
Order By: Relevance
“…We find that the oskar locus has been lost independently in some insect orders, including near-total absence from the order Hemiptera, and clarify that the absence of oskar from the Bombyx mori and Tribolium castaneum genomes (discussed in Quan and Lynch 2016) does not reflect a general absence of oskar from Lepidoptera or Coleoptera. By comparing Oskar sequences in a phylogenetic context, we reveal that distinct biophysical properties of Oskar are associated with Hemimetabola and Holometabola.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…We find that the oskar locus has been lost independently in some insect orders, including near-total absence from the order Hemiptera, and clarify that the absence of oskar from the Bombyx mori and Tribolium castaneum genomes (discussed in Quan and Lynch 2016) does not reflect a general absence of oskar from Lepidoptera or Coleoptera. By comparing Oskar sequences in a phylogenetic context, we reveal that distinct biophysical properties of Oskar are associated with Hemimetabola and Holometabola.…”
Section: Introductionsupporting
confidence: 54%
“…To date, sequences of approximately 100 oskar orthologs have been reported (Lynch, et al 2011; Jeske, et al 2015; Quan and Lynch 2016; Blondel, et al 2020). However, the vast majority of these are from the Holometabola, and it is thus unclear whether analysis of these sequences alone would have sufficient power to allow extrapolation of conservation and divergence of putative biochemical properties across insects broadly speaking.…”
Section: Introductionmentioning
confidence: 99%
“…The Drosophila oskar gene encodes a germ granule protein that is synthesized at the posterior pole of the oocyte. Oskar initiates germplasm assembly and germ cell determination; this gene appears to have been lost in the Hemiptera ( Ephrussi and Lehmann, 1992 ; Lynch et al, 2011 ; Quan and Lynch, 2016 ; Blondel et al, 2021 ). For this reason, it is expected that there should be fundamental differences in the transcriptomes of embryos during oogenesis and early embryogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Structural and biochemical studies revealed that Osk binds RNA and more recently, that it increases the helicase activity of its interaction partner Vasa [ 12 15 ]. Despite its potent activity as a germ plasm organizer, Osk homologs were not discovered outside of insect genomes [reviewed in 16 ].…”
Section: Introductionmentioning
confidence: 99%